In silico approaches for developing sesquiterpene derivatives as antagonists of human nicotinic acetylcholine receptors (nAChRs) for nicotine addiction treatment - Taufik Muhammad Fakih; Aden Dhana Rizkita; Sintia Ayu Dewi; Muchtaridi Muchtaridi (Current Research in Structural Biology)
Cinnamomum, a genus within the Lauraceae family, has gained global recognition due to its wide-ranging utility. Extensive research has been dedicated to exploring its phytochemical composition and pharmacological effects. Notably, the uniqueness of Cinnamomum lies in its terpenoid content, characterized by distinctive structures and significant biological implications. An intriguing discovery is that sesquiterpene compounds originating from Cinnamomum possess the capacity to function as antagonists for human nicotinic acetylcholine receptors (nAChRs), specifically the nAChRÿ3 subtype, rendering them potential candidates for nicotine replacement therapy (NRT) to aid active smokers. This investigation employed molecular docking and molecular dynamics simulations to assess the inhibitory effects of these compounds on nAChRÿ3. Among the 55 compounds examined, Dihydroxyeudesmene, Gibberodione, and Germacrene-E exhibited the highest binding affinities. These compounds demonstrated robust interactions with the nAChRÿ3 receptor, as evidenced by elevated molecular mechanics general surface area (MM/GBSA) values (ΔG Bind = Dihydroxyeudesmene: −36.45 kcal/mol, Gibberodione: −36.51 kcal/mol, and Germacrene-E: −36.51 kcal/mol). Molecular dynamics simulations further confirmed the stability of these three compounds, indicating their potential to effectively compete with native ligands. However, comprehensive in vitro, in vivo, and clinical investigations are imperative to ascertain the efficacy of these promising therapeutic candidates.